(untitled) ("Temas Sociais" Journal, 2024)
Although the remarks on child protection, some concerns request political action to ensure in fact the rights of the child. Literature has discussed proposals to support policymaking for reforming the Portuguese Child Protection System (CPS). This study, giving voice to CPS stakeholders, aims at assessing their level of agreement with proposals to reform the CPS and explore their positions. Research design used mixed methods, thus an online survey (n = 292), and focus groups conducted with CPS former beneficiaries, families, practitioners and academics (n = 18). Results present a clear alignment with the proposals, implicating a demanding reform towards a child-centred CPS. Emerged themes are discussed, as “Changes in legislation: strengthen family-based care”, “Changes in legislation: child-friendly justice” e “Changes in administration: restructuration of the CPS”. The conclusions highlight implications for policy.